Innovative seismic resistant structure of shield building with base isolation and tuned-mass-damping for AP1000 nuclear power plants. Issue 4 (5th June 2019) - Hou, Gangling; Li, Meng; Hai, Sun; Song, Tianshu; Wu, Lingshu; Li, Yong; Zheng, Gang; Shen, Feng; Chen, Yaodong
Abstract : Purpose: Seismic isolation, as an effective risk mitigation strategy of building/bridge structures, is incorporated into AP1000 nuclear power plants (NPPs) to alleviate the seismic damage that may occur to traditional structures of NPPs during their service. This is to promote the passive safety concept in the structural design of AP1000 NPPs against earthquakes. Design/methodology/approach: In conjunction with seismic isolation, tuned-mass-damping (TMD) is integrated into the seismic resistance system of AP1000 NPPs to satisfy the multi-functional purposes. The proposed base-isolation-tuned-mass-damper (BIS-TMD) is studied by comparing the seismic performance of NPPs with four different design configurations (i.e. without BIS, BIS, BIS-TMD and TMD) with the design parameters of the TMD subsystem optimized. Findings: Such a new seismic protection system (BIS-TMD) is proved to be promising because the advantages of BIS and TMD can be fully used. The benefits of the new structure include effective energy dissipation (i.e. wide vibration absorption band and a stable damping effect), which results in the high performance of NPPs subject to earthquakes with various intensity levels and spectra features. Originality/value: Parametric studies are performed to demonstrate the seismic robustness (e.g. consistent performance against the changing mass of the water in the gravity liquid tank and mechanical properties) which further ensures that seismic safety requirements of NPPs can be satisfied through the use of BIS-TMD.